Musculoskeletal regeneration, rehabilitation, and plasticity following traumatic injury - Greising, S. M.; Corona, B. T.; Call, J. A. (International Journal of Sports Medicine, 2020)
The musculoskeletal system has an integral role throughout life, including structural support to the body, protection, and allowing a range of fine to complex movements for daily living to elite sporting events. At various times, injuries to the musculoskeletal system occur resulting in varying levels of impact to the person both acutely and chronically. Specifically, there is a spectrum of complexity in orthopedic injuries, with some such as common muscle strains, that while burdensome will have no impact on life-long functional ability, and others that can result in long lasting disability. Focusing on extremity injuries, this review highlights: i)the current impact of orthopedic injuries in sport and daily life; ii) the foundation of bone and skeletal muscle repair and regeneration; and iii) the disruptions in regenerative healing due to traumatic orthopedic injuries. This review seeks to maximize the broad and collective research impact on sport and traumatic orthopedic injuries in search of promoting ongoing innovation for treatment and rehabilitation approaches aimed to improve musculoskeletal health throughout life.